Bamboo Reimagined : Nature Meets Design - Faridah, Sahari; Marzie, Hatef Jalil (UNIMAS Publisher, 2025)
This book is a Design Compendium showcasing bamboo-based product designs developed through design research. It presents a structured and comprehensive documentation of three categories—furniture, décor and fashion accessories that reveal bamboo’s potential for innovation, sustainability, and cultural expression, integrating traditional values with contemporary design concepts and modern lifestyle applications.